2010
DOI: 10.1103/physrevd.81.075021
|View full text |Cite
|
Sign up to set email alerts
|

LHC discovery potential of the lightest NMSSM Higgs boson in theh1a1a14μchannel

Abstract: We explore the potential of the Large Hadron Collider to observe the h 1 ! a 1 a 1 ! 4 signal from the lightest scalar Higgs boson (h 1 ) decaying into the two lightest pseudoscalar Higgs bosons (a 1 ), followed by their decays into four muons in the next-to-minimal supersymmetric standard model (NMSSM). The signature under study applies to the region of the NMSSM parameter space in which m a 1 < 2m , which has not been studied previously. In such a scenario, the suggested strategy of searching for a four-muon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…However the dominant QCD background to this signal was not identified. A more careful treatment of the dominant QCD backgrounds was carried out in [382], which concluded that the signal would still be nearly backgroundfree, with excellent prospects for discovery in early 14 TeV LHC running (considering exotic branching fractions of tens of percent).…”
Section: B Existing Collider Studiesmentioning
confidence: 99%
“…However the dominant QCD background to this signal was not identified. A more careful treatment of the dominant QCD backgrounds was carried out in [382], which concluded that the signal would still be nearly backgroundfree, with excellent prospects for discovery in early 14 TeV LHC running (considering exotic branching fractions of tens of percent).…”
Section: B Existing Collider Studiesmentioning
confidence: 99%
“…Besides, since tau decays are always accompanied by neutrinos, there is no sharp peak of a 0 1 invariant mass. For these reasons, as discussed in the literature, 4µ [39,44,45], 4γ [21,33] or 2γ + 2-jets [46] search channels with m a 0 1 < 2m τ turn out to be the ideal way to probe NMSSM Higgses with very light pseudoscalars.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that gluon fusion and b-quark fusion are the two main production processes of a Higgs at the LHC in the context of SUSY. Gluon fusion dominates over b-quark fusion in our benchmark points, as can be shown using the relevant equations [44]:…”
Section: Jhep10(2011)020mentioning
confidence: 63%